Sunnhemp breeding: Challenges and prospects - BHANDARI, H R; TRIPATHI, M K; CHAUDHARY, BABITA; SARKAR, S K (The Indian Journal of Agricultural Sciences, 2016)
Sunnhemp (Crotalaria juncea L.) is an important fibre crop of tropical and sub-tropical parts of the world and has multiple uses. With the commercialization of agriculture, major food crops and cash crops gained momentum and fibre crops, particularly sunnhemp lagged behind on account of increased availability of cheap synthetic fibres. In the present context, the cultivation of sunnhemp is limited to marginal lands and with minimum inputs. Subsequently, the production and productivity of the crop has declined. Productivity of sunnhemp can be increased by genetic improvement of the crop. However, very little reports are available detailing genetics of different economic traits. Hence, an attempt is being made to collect all the scattered relevant genetic information in order to make the information useful in expediting the genetic improvement of the crop.